The impact of children on female earnings in Britain - Tarja K. Viitanen (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper examines the impact of children on female wages in the UK using the National Child Development Study. Empirically this involves using an extension of the Roy model, which simultaneously corrects for the endogeneity of labour force participation and fertility. The wage differential between women without children and women with children is estimated to range between 19% and 22% not accounting for endogeneity. This result confirms the findings of many previous studies, however, the results indicate substantial non-random selection into employment for women hence leading to biased OLS estimates. The wage differential reduces to 16%-18% instrumenting participation and fertility, however, using the estimates obtained from the double-selection model, the wage differential between mothers and childless women reduces to just 10%-13%.
Keywords: J13; J22; 330; female labour supply; fertility; wage differentials; Frauenarbeitslohn; Lohnstruktur; Kinder; Mütter; Schätzung; Grossbritannien